FROM ASSESSMENT EX POST TO EX ANTE ESTIMATES: RISKS ANALYSIS OF AGRICULTURAL DEVELOPMENT PROJECTS IN ALGERIA (International Journal of Engineering Sciences & Management Research, 2018)
Today, investors want a larger visibility on the validity of time limits and on potential financial losses. The study concerns the risk analysis of agricultural projects. On a sample of project achieving enterprises working in wilayas belonging to three zones: mountain, steppe and desert, a qualitative analysis made to assess the severity of the causes of risks and a quantitative analysis made on several simulations during the achievement of the project by random edition ( type Monte Carlo simulation leading to cumulated probability distributions, it will result a classification of potential risks and an assessment of contingency reserves for risks ( time limits, cost ) for parts of works of the project. These results highlight the importance of the risk analysis in the full success of the project management